Menganalisis Efektivitas Metode Evaluasi Pembelajaran di Sekolah Dasar Tinjau terhadap Kinerja Siswa dan Peningkatan Prestasi Belajar - Aprilya, Anggi; Setyani, Gading Retna Tri; Pitaloka, Nadia Rinjani; Cahyani, Septia Putri (Lembaga Yasin AlSys, 2023)
This study aims to analyze the effectiveness of elementary school learning evaluation methods and their impact on students' performance and their improvement in learning performance. Evaluation methods used in learning have an important role in measuring students' understanding and providing constructive feedback. However, there are not many studies that specifically consider the effectiveness of evaluation methods at the elementary school level. In this study, the research method used is qualitative descriptive research. Data were collected through class observation, interviews with teachers, and analysis of related documents. Research results show that there are various evaluation methods used by teachers in elementary school, including writing tests, verbal tests, project tasks, portfolios, and direct observation. In the context of learning evaluation, it was found that evaluation methods involving students' active involvement, providing constructive feedback, and measuring in-depth understanding and application of knowledge in real contexts had a positive impact on students' performance and their improvement in learning performance. Methods such as project tasks and portfolios provide students with opportunities to develop critical thinking skills, creativity, and collaboration. Recommendations made based on this study were to involve teachers in training and developing effective evaluation methods, encouraging the use of variations in evaluation methods, utilizing technology in the evaluation process, and promoting collaboration between teachers and students in the evaluation process. This study contributes significantly to our understanding of the effectiveness of elementary school evaluation methods. By implementing effective evaluation methods, elementary schools can create a learning environment that motivates, collaborates, and focuses on students' holistic development.